Health‐related quality of life of children with low language from early childhood to adolescence: results from an Australian longitudinal population‐based study. (2nd June 2020) - Le, Ha N.D.; Mensah, Fiona; Eadie, Patricia; McKean, Cristina; Sciberras, Emma; Bavin, Edith L.; Reilly, Sheena; Gold, Lisa
Abstract : Background: Low language abilities are known to be associated with significant adverse long‐term outcomes. However, associations between low language and health‐related quality of life (HRQoL) are unclear. We aimed to (a) examine the association between low language and HRQoL from 4 to 13 years and (b) classify the children's trajectories of HRQoL and language and examine the association between language and HRQoL trajectories. Methods: Data were from an Australian community‐based cohort of children. HRQoL was measured at ages 4–13 years using the parent‐reported Pediatric Quality of Life Inventory 4.0. Language was assessed using the Clinical Evaluation of Language Fundamentals (CELF)‐Preschool 2nd edition at 4 years and the CELF‐4th edition at 5, 7 and 11 years. Multivariable linear regression and mixed effect modelling were used to estimate cross‐sectional and longitudinal associations between low language and HRQoL from 4 to 13 years. A joint group‐based trajectory model was used to characterize associations between HRQoL and language trajectories over childhood. Results: Children with low language had substantially lower HRQoL than children with typical language from 4 to 13 years. Higher language scores were associated with better HRQoL, particularly in social and school functioning. Three HRQoL trajectories were identified: stable‐high (51% of children), reduced with slow decline (40%) and low with rapid decline (9%). Children with low language were less likely to follow a stable‐high HRQoL trajectory (40%) while 26% and 34% followed the reduced with slow decline and low with rapid decline trajectories, respectively. Conclusions: Children with low language experienced reduced HRQoL from 4 to 13 years. More than half had declining trajectories in HRQoL highlighting the need to monitor these children over time. Interventions should not only aim to improve children's language ability but also address the wider functional impacts of low language.